Análisis de la situación del aula pedagógica hospitalaria del Hospital Isidro Ayora de la ciudad de Loja, periodo 2021-2022 - González Muñoz, Jessica Denisse (2022)
The present Curricular Integration Work called: Analysis of the situation of the hospital pedagogical classroom of the Hospital Isidro Ayora, the objective was, to describe the pedagogical situation of the hospital classroom of the Hospital Isidro Ayora to know educational processes and integration to the school system of students in condition of illness; The participants were the coordinator and two teachers, two psychologists of the DECE; a survey and interviews were applied, and the following results were found from this analysis: the functioning of the hospital classroom as a learning environment lacks effectiveness due to the failure of the treating physician to refer the hospitalized minor to the program so that he/she can immediately enter the hospital pedagogical classroom for intervention and pedagogical follow-up; In addition, the main actors are identified, one of them is the coordinator and also teachers with the profile of educational psychologists; as for the axes of intervention in the pedagogical hospital classroom that are declared in the National Model of Management and educational care in hospital and at home, only a minimum compliance in the axes is observed; The lack of internal regulations that fulfill the mission of organizing and regulating its operation is evident; The absence of services, the inadequate pedagogical environment, the lack of didactic materials and the lack of adequate methodologies for learning diminish the effectiveness of the school process. Finally, the requirements that sick students must meet to be attended, according to the law, all school patients must be admitted from the age of three, and it is evident that the teachers try to comply with this requirement by following up at home after discharge. Hospital pedagogical care should aim to improve the quality of the educational process during hospitalization, help them throughout the disease process, and prepare them for reincorporation into daily school and family life. Keywords: home care, pedagogical classroom, integration, school reintegration, pedagogy